The Influence Of Work Stress, Work Motivation, Work Environment On The Performance Of Health Workers In 24-Hour Non-Inpatient Community Health Centers In Wonocolo District, Surabaya With Job Satisfaction As An Intervening Variable - Pribadi, Andry; Sukoco, Agus; Suyono, Joko (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: his study aims to analyze the influence of work stress, work motivation, and work environment on the performance of healthcare workers at 24-Hour Non-Inpatient Community Health Centers in Wonocolo District, Surabaya. The study also explores the impact of these three factors on job satisfaction and examines the role of job satisfaction as an intervening variable in the relationship between work stress, work motivation, and work environment on the performance of healthcare workers. This research adopts a quantitative approach using a survey method with 90 healthcare workers as the sample. Data collection was conducted through questionnaires, and data analysis was carried out using Structural Equation Modeling (SEM). The results of the study indicate that out of ten hypotheses tested, three hypotheses were accepted. Work stress has a significant negative effect on healthcare workers' performance (P = 0.000), work motivation has a significant positive effect on job satisfaction (P = 0.001), and the work environment has a significant positive effect on job satisfaction (P = 0.003). Other hypotheses, such as the direct effects of work stress, work motivation, and work environment on performance and job satisfaction, were rejected as they did not meet the significance threshold of P < 0.05. The limitations of the study include the small sample size and the use of questionnaires, which may be influenced by respondents' subjective bias. Future research is expected to involve a larger sample and additional variables. Design/methodology/approach: The technique for collecting data involved using questionnaires that were completed through the Saturated Sampling method. These questionnaires were distributed to a sample of 90 healthcare workers at the Community Health Centers in Wonocolo District, Surabaya, and the data was analyzed using the SEM-PLS application. Findings: The results indicate that work stress negatively affects the performance of healthcare workers. Work motivation does not considerably impact the performance of healthcare workers. Also, the work environment has no major influence on their performance. Work stress does not noticeably affect job satisfaction. On the other hand, work motivation has a positive effect on job satisfaction. What's more, the work environment plays a major role in determining job satisfaction. Job satisfaction, however, does not considerably affect the performance of healthcare workers and does not act as a mediator in the relationship between work stress, work motivation, the work environment, and healthcare worker performance. Originality/value: This study contributes to understanding the factors influencing healthcare worker performance at the Surabaya Regional Health Laboratory. It highlights that while work stress negatively impacts performance, work motivation positively affects job satisfaction, and the work environment significantly influences job satisfaction. However, job satisfaction does not substantially impact performance and does not mediate the relationships between work stress, work motivation, the work environment, and performance. This insight emphasizes the need for targeted strategies to address work stress and motivation to enhance employee outcomes. Paper type: Research paper